2008
DOI: 10.1111/j.1365-2826.2008.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Central Versus Peripheral Antagonism of Cannabinoid CB1 Receptor in Obesity: Effects of LH‐21, a Peripherally Acting Neutral Cannabinoid Receptor Antagonist, in Zucker Rats

Abstract: The endocannabinoid system as a new modulator of feeding and energy expenditureThe endogenous cannabinoid system is a lipid signalling system comprising arachidonic acid derivatives (N-acylethanolamides and 2-arachidonoyl glycerol and related compounds) that has recently been identified as a major homeostatic system in brain and peripheral tissues. The N-acylethanolamides anandamide and oleoylethanolamide (OEA) are lipid mediators that regulate feeding, lipid metabolism and energy balance. Both of them can sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 34 publications
4
67
0
Order By: Relevance
“…Additionally, this combinational therapy reduces the hepatic steatosis observed in obese rats, decreasing liver fat depots and improving liver function [133]. A similar effect has been observed with the combination of LH-21 and OEA [102].…”
Section: Efficacy Of Combined Therapy For Obesitysupporting
confidence: 54%
See 1 more Smart Citation
“…Additionally, this combinational therapy reduces the hepatic steatosis observed in obese rats, decreasing liver fat depots and improving liver function [133]. A similar effect has been observed with the combination of LH-21 and OEA [102].…”
Section: Efficacy Of Combined Therapy For Obesitysupporting
confidence: 54%
“…LH-21 displays a different pharmacological profile in comparison with rimonabant [101,102]. Acute administration of this compound reduces food intake in fasted rats [101].…”
Section: Peripherally Restricted Cb 1 Receptor Antagonistsmentioning
confidence: 99%
“…8 SR141716A (N-(piperidin-1-yl)-5-4-chlorophenyl)-1-2,4-dichlorophenyl)-4-methyl-1H-pyrazole-3-carboxamide hydrochloride) (code name for rimonabant, withdrawn from the markets since October 2008), a CB1-receptor antagonist and also classified as an inverse agonist, modulates food intake by acting on CB1 receptors located on capsaicin-sensitive sensory terminals. 9 Pavon et al 10,11 demonstrated that LH-21, a peripherally acting neutral CB-receptor antagonist, has antiobesity effects in vivo. Thereafter, Chen et al 12 suggested that LH-21 does not act on the CB1 receptor to inhibit food intake in mice.…”
Section: Introductionmentioning
confidence: 99%
“…23 At present, different cannabinoid ligands have been identified, 24,25 which can be classified into different chemical families. [27][28][29][30] Among the different classes of synthetic compounds assuring CB 1 or CB 2 affinity and selectivity, the relevance of pyrazole derivatives has been consolidated by various studies and the pyrazole moiety is regarded as a versatile scaffold in the cannabinoid research field.…”
Section: Introductionmentioning
confidence: 99%
“…MS (10), 171 (100), 160 (7), 145 (5), 124 (4), 96 (2), 64 (13). HRMS-EI m/z for C 30 4; and 0.1% BSA). The homogenates were centrifuged at 3000 rpm for 10 min, and the supernatants were then recentrifuged at 18000 rpm for 10 min.…”
mentioning
confidence: 99%